Survival Prognosis, Tumor Immune Landscape, and Immune Responses of ADAMTS14 in Clear Cell Renal Cell Carcinoma and Its Potential Mechanisms - Chen, Yinhao; Ji, Hao; Liu, Shouyong; Xing, Qianwei; Zhu, Bingye; Wang, Yi (Frontiers in Immunology, 2022)
Background: ADAMTS14 played a crucial role in the formation and development of various cancers. Currently, no associations had been revealed between ADAMTS14 and clear cell renal cell carcinoma (ccRCC). Hence, this study was designed to assess the prognostic values and immunological roles of ADAMTS14 in ccRCC and to reveal its potential mechanisms. Methods: ADAMTS14-related expression profiles and related clinical data were downloaded from The Cancer Genome Atlas (TCGA) dataset, validated by ICGC dataset, qRT-PCR, immunohistochemistry. We utilized gene set enrichment analysis (GSEA) to find potentially ADAMTS14-related pathways and applied univariate/multivariate Cox regression analyses to identify independent factors significantly related to overall survival (OS) for ccRCC. A nomogram consisted of independent prognostic factors was also conducted. We further explored the associations between ADAMTS14 with immunity and revealed its potential mechanisms. Results: ADAMTS14 displayed a higher expression in ccRCC tumor than in adjacent normal tissues, and further validated results of ICGC dataset, qRT-PCR and immunohistochemistry remained consistent (all P <0.05). Moreover, elevated ADAMTS14 expression was significantly associated with poor OS (P <0.001). Through univariate/multivariate Cox regression analyses, ADAMTS14 was found to be an independent prognostic factor for ccRCC (both P <0.05) and GSEA identified several signaling pathways including INSULIN, MTOR, PPAR pathways, and so on. The nomogram based on independent prognostic factors was successfully established and well evaluated. Moreover, the expression of ADAMTS14 was remarkably associated with immune checkpoint molecules, tumor mutational burden (TMB), immune cells and tumor immune microenvironment (all P <0.05). Results from TIDE and TCIA showed that highly expressed ADAMTS14 could predict worse efficacy of immunotherapy (all P <0.05). As for its potential mechanisms, several LncRNA/RNA binding protein (RBP)/ADAMTS14 mRNA networks were also revealed by us. Conclusions: ADAMTS14 was found to play oncogenic roles in ccRCC and to be significantly associated with immunity. Several LncRNA/RBP/ADAMTS14 mRNA networks were also identified for its potential mechanisms.